AUGMENTED REALITY WISATA MONUMEN BERSEJARAH LAMPUNG BERBASIS MOBILE - Triowali Rosandy; Hermanto -; TM Zaini (Jurnal Informatika, 2019)
Development of 'Virtual' Tourism This historical monument of Lampung-based Mobile is projected as an innovation of socialization and exploration of historical monuments using attractive, informative and interactive computer graphics technology, because it can bring imitation of objects that are socialized so that tourists or visitors can interact and see the beauty directly historical monument objects which are products of national culture.In contrast to conventional promotions, the technology that will be applied is interactive and more interesting because the information that can be displayed is not only in the form of text and images that are usually found on a website, but also can display 3D objects, as well as animation in real time, so that tourists by using this mobile-based technology as if it can be directly and react with the historical monument of Lampung that is accessed. It is hoped that the application of computer graphics technology to tourism objects can support the dissemination of Indonesian cultural products to the international realm, which is one of the information technologies that is expected to be able to contribute positively to the preservation of Indonesian cultural products. This computer application development was developed using one of the software development methods, namely 'waterfall'. In this study, a series of activities will be carried out such as surveys, observations in order to obtain information on system requirements, design and proceed with the implementation stage by modeling 3D objects of the historical Lampung monument. Furthermore, integration is carried out on the unity application. At the next stage mobile testing is carried out. Keywords - Tourism, virtual object, mobile, monument building